Analisis Efektivitas Penanganan Piutang dengan Bilyet Giro di PT. YNT - Putri, Yohana Nandiva; Yuhertiana, Indrawati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effectiveness of accounts receivable management using Bilyet Giro (BG) at PT YNT. The research focuses on administrative procedures such as invoice creation, amount verification, stamp duty application, internal approval, and the distribution of documents, including invoices, delivery orders, and transmittals. A qualitative approach was adopted with a case study method, and data was collected through in-depth interviews with finance division staff. The findings indicate that the BG-based receivables management system at PT YNT has been implemented with structured procedures. However, several challenges were identified, such as delays in document distribution and reliance on manual approval processes, which hinder the efficiency of the administration flow. The company has taken corrective actions, such as the implementation of digital archiving and improved interdepartmental coordination. These findings offer insights into the effectiveness of the current receivables management system and provide recommendations for further improvements. The research is expected to contribute to internal evaluations and enhance operational efficiency at PT YNT, improving the accuracy and reliability of the accounts receivable management and internal control systems.